A spatio-temporal analysis of cropping pattern, crop diversification and production in Tarai region of Uttar Pradesh - Ashutosh Kumar Chaurasia; Alok Kumar Choubey; Gayatri Rai (National Geographical Journal of India, 2021)
Agriculture remains the most important occupation and source of livelihood for the majority of the population in our country. The study of cropping patterns, diversification and production is important in agricultural development. Cropping pattern is the proportion of area under various crops while crop diversification refers to the raising of various crops. Agricultural productivity is an input-output ratio that facilitates efficient comparison. These concepts are influenced by various geo-climatic, socio-economic and institutional factors. Tarai region is a marshy moist area lying between Himalayan foothills and Gangetic plains. In Uttar Pradesh, the region extends over 7 districts from Pilibhit to Maharajganj. This region is predominantly agrarian. The present paper aims to study the cropping pattern, Spatio-temporal pattern of crop diversification and production of crops at the district level in the Tarai region of Uttar Pradesh for the period of 2007-08 to 2017-18. The study is based on agricultural data collected from Statistical Abstract of Uttar Pradesh. 13 crops under 4 categories are selected in total. The study uses the location quotient technique for calculating crop concentration, the Gibbs-Martin (1962) method for calculating crop diversification and other statistical measures for analysis. It was found that cropped area of the region has decreased in the reference period and the region is dominated by the cultivation of cereal crops and sugarcane. Low crop diversification was recorded in the region due to similar physical conditions and the practice of traditional agriculture. Production and productivity of crops have greatly increased primarily due to the increasing production of sugarcane. It is believed that the present study will help ascertain the ground reality of agriculture in the study region.